Isaac Newton and the laws of motion - Gianopoulos, Andrea, author; Miller, Phil, illustrator; Barnett, Charles, illustrator (London : Raintree Publisher, 2007)
"In dramatic graphic novel format, Isaac Newton and the Laws of Motion tells the story of the scientist who came up with the maths to explain how nature works. The book takes you through Newton's life and times, from building simple machines as a boy, to his life as a student, tot he observations that became the basis for his Laws of Motion."--Back cover.